Healthcare Rights of Indigenous Australians with Kidney Disease: A Framework Analysis of Renal Policies and Strategic Plans for the Northern Territory Health Services - Panicker, Leena; Tofa, Matalena; Lowell, Anne (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2026)
This qualitative research, the first Australian study of its kind, constitutes an in-depth analysis of kidney disease care policies and strategic plans (n=11) to identify how they recognise and affirm the healthcare rights of the Northern Territory’s (NT) Indigenous People. The Australian Charter of Healthcare Rights was used as a guiding document for the research. The study employed a thematic analysis method, specifically the framework analysis, due to its suitability for identifying and analysing patterns in qualitative data. The findings revealed that the Indigenous People’s healthcare rights are not explicitly addressed in the policies and plans, even though they constitute 89% of the kidney disease patient population in the NT. A salient aspect of every policy and strategic plan was the lack of specific affirmative actions and targets to evaluate renal care processes and progress for Indigenous Peoples.